Histological and Clinical Stage Profiles of Young-aged Breast Carcinoma - Alda Vania Sugiarto Hadiyanto; Ika Pawitra Miranti; Yan Wisnu Prajoko; Hermawan Istiadi (Diponegoro International Medical Journal, 2022)
Background: Breast cancer is the most common type of malignancy in women. Many studies report that the characteristics and prognosis of young-aged breast carcinoma are worse than in old age. Data on young-aged breast carcinoma in Indonesia is relatively lacking and always needs updates.Objective: To determine the incidence and distribution based on histological profiles and clinical stage, as well as the association between molecular subtype with grade and clinical stage of young-aged breast carcinoma (<40 years old) at Dr. Kariadi General Hospital Center in 2018-2020.Methods: This research was an observational descriptive study using medical records of young-aged breast carcinoma patients which were recorded at Dr. Kariadi General Hospital Center from 1st January 2018 until 31st December 2020. The data were processed with Microsoft Excel and SPSS.Results: The results showed that there were 110 patients consisting of 25 people in 2018, 37 people in 2019, and 48 people in 2020. The most common histological and clinical stage was IBC-NST with 75 people (68,18%), Luminal B with 53 people (48,18%). grade II with 71 people (64,65%), and stage IV with 45 people (40,09%). There is a significant association between molecular subtype and grade (p=0.003). There is no significant association between molecular subtype and clinical stage (p=0.704).Conclusion: The incidence of young-aged breast carcinoma at Dr. Kariadi General Hospital Center in 2018-2020 was increasing every year. The most common histological profiles and clinical stage during that period were IBC-NST, Luminal B, grade II, and stage IV. There is a significant association between molecular subtype and grade.Keywords: Breast carcinoma, clinical stage, grade, histological type, molecular subtype, young age